Umiejętność poszukiwania hiperonimów o wysokim poziomie ogólności przez osoby niewidome i widzące - Mikołajczak-Matyja, Nawoja (Investigationes Linguisticae, 2004)
The ability of searching for hypernyms with a high degree of generality by persons with impaired eyesight and the blind is thoroughly described. The present paper concerns the hierarchically organised structure of the mental lexicon. The final elements of hierarchical series of hypernyms constructed for 75 Polish nouns by 116 subjects (58 blind people and 58 sighted people) were analysed and compared.